2017
DOI: 10.1007/s11136-017-1719-x
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality and subjective well-being: a systematic review and meta-analysis

Abstract: BackgroundReducing income inequality is one possible approach to boost subjective well-being (SWB). Nevertheless, previous studies have reported positive, null and negative associations between income inequality and SWB.ObjectivesThis study reports the first systematic review and meta-analysis of the relationship between income inequality and SWB, and seeks to understand the heterogeneity in the literature.MethodsThis systematic review was conducted according to guidance (PRISMA and Cochrane Handbook) and sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 63 publications
5
96
1
1
Order By: Relevance
“…In line with previous studies (e.g. Ngamaba et al 2018), we found no effect of income inequality on SWB. Nevertheless, previous research showed that income inequality has a negative effect on life satisfaction inequality as well as on social trust (Graafland and Lous 2019), which implies that reducing income inequality can be a desirable goal after all (see also Deeming and Jones 2015: 277).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous studies (e.g. Ngamaba et al 2018), we found no effect of income inequality on SWB. Nevertheless, previous research showed that income inequality has a negative effect on life satisfaction inequality as well as on social trust (Graafland and Lous 2019), which implies that reducing income inequality can be a desirable goal after all (see also Deeming and Jones 2015: 277).…”
Section: Discussionsupporting
confidence: 93%
“…Income inequality on the other hand, measured by the Gini coefficient, is not related to SWB. This is in accordance to previous literature (Di Tella et al 2001;Lopes et al 2014;Ngamaba et al 2018).…”
Section: Control Variablessupporting
confidence: 94%
“…A recent systematic review on the inequality-wellbeing relationship (Ngamaba, Panagioti, & Armitage, 2018) argues that the inconsistent or inconclusive findings in the literature can be explained by the fact that the strength and direction of the inequality-wellbeing relationship is mediated by several other factors. Thus, Ngamaba, et al (2018) emphasise the importance of examining the factors through which inequality influences wellbeing. For instance, social capital and trust is a channel of influence that has received much attention in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…These are often associated in the current literature. In fact, the link between subjective well‐being and material prosperity is a topic of controversy between economists and other experts of the topic (see Ngamaba, Panagioti and Armitage for a comprehensive review; on this topic, see also Hall and Lamont ). Nor do I embrace a focus on individual grit.…”
Section: ‘It's the Economy Stupid’ And Other Points Of Divergencementioning
confidence: 99%